Managing oil revenue in Ghana: Controlling spending is the key - Diao, Xinshen; Breisinger, Clemens (International Food Policy Research Institute, 2010)
With an average growth rate of 5 percent and a reduction of poverty by one-half over the past two decades, Ghana is a recent success story and a rising star in African development. Yet the country remains dependent on relatively few external sources of income and its external debt has started to rise again (IMF 20081). The recent discovery of offshore oil is seen by many as an important new source of income, and an opportunity to overcome persisting structural weaknesses in exports and the economy as a whole, and raise Ghana's prospects of becoming a frontrunner in African development.